Lived Experiences of English Pre-Service Teachers on Public Speaking Anxiety: A Speech Improvement Program - Arman Navarro (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2025)
This study explored the lived experiences of 10 English pre-service teachers with public speaking anxiety. Hermeneutic phenomenology guided the qualitative research design, employing interviews and focus group discussions to gather data. Findings revealed seven key themes: language skill gaps, attitudes toward second language learning, low self-confidence hindering speaking, improved teaching strategies, the importance of a supportive, nonjudgmental environment, and the influence of varied internal and external factors on anxiety. The study highlights the need for educators to foster supportive learning environments that mitigate anxiety and encourage confident public speaking. To address this, the researcher proposes